Interpersonal Relationships and Suicidal Ideation in Youth with Bipolar Disorder - Sewall, Craig J.R. (Arch Suicide Res, 2019)
OBJECTIVES: Examine how relationship quality in family and peer domains are associated with suicidal ideation (SI) in youth with Bipolar Disorder (BP). METHODS: 404 Course and Outcome of Bipolar Youth study participants were assessed for psychiatric disorders and SI at intake, and family/peer relationships the month after intake. Multivariate logistic regression examined associations between relationships and SI, controlling for significant covariates. RESULTS: 144 youth (36%) reported SI at intake; bivariate analyses indicated they had significantly worse family/peer relationships. Multivariate analyses showed family/peer relationships were associated with current SI, controlling for significant covariates. CONCLUSION: Results support associations between poor relationships and SI in BP youth, regardless of current mood symptom severity. Clinicians should assess relationships when completing risk assessments with BP youth.